Genetic diversity of Chinese indigenous sheep breeds inferred from microsatellite markers - Zhong, T.; Han, J.L.; Guo, J.; Zhao, Q.J.; Fu, B.L.; He, X.H.; Jeon, J.T.; Guan, Wei-Jun; Ma, Y.H. (Elsevier, 2010)
To determine the genetic diversity and phylogenetic relationships among Chinese sheep, 10 indigenous breeds and one introduced breed were genotyped for 19 microsatellite loci. The mean number of alleles per breed ranged from 5.44 (Guide Black Fur sheep) to 9.13 (Ujumqin sheep and Hulunbeier sheep), the expected heterozygosity varied from 0.623 (Guide Black Fur sheep) to 0.737 (Zhaotong sheep), and the allelic richness ranged from 5.169 (Guide Black Fur sheep) to 7.610 (Zhaotong sheep). The deviation from Hardy–Weinberg equilibrium (HWE) was statistically significant (P < 0.05) at three loci (SRCRSP5, OarAE129 and DYMS1) in most of the breeds. Chinese sheep breeds had maintained a high level of within-population genetic differentiation (95.23%), with the remainder explained by differentiation among populations (4.77%). The genetic differentiation pattern and genetic relationships among Chinese sheep breeds displayed a high consistency with the traditional classification. Both the Bayesian cluster and principal component analyses showed a reliable clustering pattern, which revealed three major clusters in Chinese indigenous sheep (Mongolian sheep, Kazakh sheep and Tibetan sheep), except Zhaotong and Guide Black Fur sheep. There were probably caused by different breeding history, geography isolation and different levels of inbreeding. This study will help to interpret the genetic characters of Chinese indigenous sheep and benefit to the future conservation programs.